Multiply both sides of first equation by 2
6 x + 4 y = 14
Multiply both sides of second equation by 3
6 x - 9 y = - 12
6 x + 4 y = 14
-
6 x - 9 y = - 12
___________
0 + 4 y - ( - 9 y ) = 14 - ( -12 )
4y + 9 y = 14 + 12
13 y = 26
Divide both sides by 13
y = 2
Replace y with 2 in first equation:
3 x + 2 ∙ 2 = 7
3 x + 4 = 7
Subtract 4 to both sides
3 x = 3
x = 1
Or replace y with 2 in second equation:
2 x - 3 ∙ 2 = - 4
2 x - 6 = - 4
Add 6 to both sides
2 x = 2
x = 1
The solution is x = 1 , y = 2
You can write the solution as ( 1 , 2 )
3x+2y=7
2x-3y=-4
1 answer